The Effect Of Non-Physical Work Environment, Motivation and Work Discipline On Employee Performance at Pt. Fajar Agung - Astuti, Widya; Mardhiyah, Ainun (Simangunsong : Journal of Business Administration, Management, Economic And Accounting, 2023)
Performance is the implementation of work both in quality and quantity that has been achieved by the workforce with a predetermined period of time in doing work in accordance with the obligations that have been imposed on employees. At PT. Fajar Agung, it is known that employee performance is not optimal, it can be seen from the non-physical work environment, employees are still less cohesive at work and work interaction between superiors and employees is still lacking, besides the motivation given by the leadership is not enough to satisfy employees, and in work discipline. still said to be not good because there are still many employees who are not disciplined at work. The purpose of this study is to determine the effect of non-physical work environment, motivation and work discipline on the performance of employees of PT. Great Dawn. This study uses quantitative research methods with an associative approach. The population in this study are employees of PT. Fajar Agung as many as 173 permanent employees. Sampling was done by non-probability sampling using a perceptive sampling technique and with a sample of 64 respondents. The primary data used in this study was obtained by distributing questionnaires directly to employees, while the secondary data was obtained through a literature study. The data analysis method used is validity test, reliability test, classical assumption test, multiple linear regression test, and hypothesis testing using SPSS. The results of this study indicate that the non-physical work environment, motivation and work discipline have a positive and significant effect either partially